Lysosome (Dys)function in Atherosclerosis—A Big Weight on the Shoulders of a Small Organelle - Marques, André R.A. (2021)
Funding: This research was supported by the research project PTDC/MEDPAT/29395/2017, financed by national funds through the Fundação para a Ciência e Tecnologia (FCT) and by PROGRAMAS DE ATIVIDADES CONJUNTAS (PAC), Reference: No. 03/SAICT/2015. AM was supported by the CEECIND/01006/2017, funded by FCT. This manuscript was supported by the LYSOCIL project, which has received funding from the European Union’s Horizon 2020 Research and Innovation Programme under grant agreement no. 811087.